Meningkatkan Kesadaran Masyarakat Tentang Risiko Pinjaman Online Dan Judi Online - Rochmah, Zeshinta Adelia Nur; Rohmah, Wahyu Miftakhul Fitri Nur (NAJWA: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2025)
The development of digital technology has given rise to new problems in the form of misuse of digital financial services. Some examples include illegal online lending (pinjol) and online gambling. Teenagers, who frequently use digital technology, are highly vulnerable to unregulated illegal pinjol and judol practices not supervised by the OJK. The objective of this initiative is to raise teenagers' awareness of the dangers of illegal lending and online gambling through an educational approach that is both enjoyable and participatory. The implementation methods included face-to-face counseling, case discussions, and interactive question-and-answer sessions held in Mekikis Village, Purwoasri Subdistrict, involving 35 teenagers. The materials presented included an introduction illegal online lending and online gambling, their illegal characteristics, psychological and social effects, and prevention methods. The results of the activity showed an increase in participants' understanding, marked by active engagement in discussions, the ability to recognize the characteristics of illegal online lending, and a commitment to share information with family and the surrounding community. Thus, this educational program was effective in building digital literacy and critical awareness among teenagers about the dangers of illegal online lending and online gambling.